KORELASI ANTARA KONSEP DIRI DENGAN PERCAYA DIRI SISWA MTs. ISLAHIL ATFAL RUMAK - Sukarman Sukarman (Jurnal Ilmiah Mandala Education (JIME), 2017)
Based on the initial survey on April 2016 that the concept of self-study sites the students in MTs. Islahil Atfal Rumak still lacking. This will be illustrated by the many students who are not active in learning and lack of communication in learning which of course have an impact on the confidence of students. While the objectives of this research was to determine whether there is a relationship self-concept and confidence of students in MTs. Islahil Atfal Rumak. The method used in the determination of the research subject with Random Sampling with a study population of 104 students. the sample used is 25% of the amount that is 26 students. Methods of data collection in this study the methods of questionnaires and documentation as the principal method, and the method of interviews and observations as a complementary method. While the method of data analysis using product moment correlation. Results of the analysis of the data obtained at 0.394 while the value table at 0.388 at significance level of 5%. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The conclusion from this study is that there is a relationship between self-concept and confidence of students with a description of the results of data analysis that r count larger than r table (0.393> 0.388), in which the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted in other words, these results significantly